Enhancing carbon sequestration and greenhouse gas mitigation in semiarid farmland: The promising role of biochar application with biodegradable film mulching - Jinwen Pang; Zhonghong Tian; Mengjie Zhang; Yuhao Wang; Tianxiang Qi; Qilin Zhang; Enke Liu; Weijun Zhang; Xiaolong Ren; Zhikuan Jia; Kadambot H.M. Siddique; Peng Zhang (Journal of Integrative Agriculture, 2025)
Long-term mulching has improved crop yields and farmland productivity in semiarid areas, but it has also increased greenhouse gas (GHG) emissions and depleted soil fertility. Biochar application has emerged as a promising solution for addressing these issues. In this study, we investigated the effects of four biochar application rates (no biochar (N)=0 t ha–1, low (L)=3 t ha–1, medium (M)=6 t ha–1, and high (H)=9 t ha–1) under film mulching and no mulching conditions over three growing seasons. We assessed the impacts on GHG emissions, soil organic carbon sequestration (SOCS), and maize yield to evaluate the productivity and sustainability of farmland ecosystems. Our results demonstrated that mulching increased maize yield (18.68–41.80%), total fixed C in straw (23.64%), grain (28.87%), and root (46.31%) biomass, and GHG emissions (CO2, 10.78%; N2O, 3.41%), while reducing SOCS (6.57%) and GHG intensity (GHGI; 13.61%). Under mulching, biochar application significantly increased maize yield (10.20%), total fixed C in straw (17.97%), grain (17.69%) and root (16.75%) biomass, and SOCS (4.78%). Moreover, it reduced the GHG emissions (CO2, 3.09%; N2O, 6.36%) and GHGI (12.28%). These effects correlated with the biochar addition rate, with the optimal rate being 9.0 t ha–1. In conclusion, biochar application reduces CO2 and N2O emissions, enhances CH4 absorption, and improves maize yield under film mulching. It also improves the soil carbon fixation capacity while mitigating the warming potential, making it a promising sustainable management method for mulched farmland in semiarid areas.